Design for Highly Efficient Nanometagratings and Theory of Extreme Subdiffraction Photon Control. Issue 11 (2nd August 2022) - Gao, Yan-ming; Yu, Xiang-yang
Abstract : Conventional planar metasurfaces are always much larger than the wavelength level. Previous studies on extreme wavefront control based on superoscillation suggest a fundamental tradeoff between the size and efficiency of diffraction‐based metasurfaces. Herein, the theory of extreme subdiffraction photon control is proposed and the abnormal wave propagation phenomenon supporting logical design for highly efficient metasurfaces of subwavelength size is pointed out. A new class of novel metasurfaces named nanometagratings is demostrated, which is smaller than one wavelength, and manages to achieve arbitrary wavefront engineering with high conversion efficiency, enabling extreme photon control within subwavelength scale. The theoretical approach is expected to open the avenue for ultrasmall highly efficient functional metasurfaces and promises novel applications such as highly integrated on‐chip quantum optical information computation. Abstract : Theories enabling nanosized metasurfaces to break through the diffraction limit and achieve arbitrary wavefront control beyond the near field with near‐unitary conversion efficiency are proposed. A new class of ultrasmall metasurfaces called nanometagratings is demonstrated to achieve highly efficient subdiffraction wavefront engineering within subwavelength scale, promising nanosized on‐chip photon gates.